Caring for patients who are deaf or hard of hearing. Issue 12 (December 2015) - Brown, Heather L.; Hughes-Bell, Aileen; McDuffie, Anna W.
Abstract : ABSTRACT: Patients who are deaf and hard of hearing often find the American healthcare system to be inaccessible due to communication barriers. This article describes facilities' and providers' requirements under the Americans with Disabilities Act to provide qualified interpreters and other assistive devices to patients who are deaf or hard of hearing. Removing communication barriers can protect healthcare providers from potential legal action and lets them deliver consistent, quality healthcare to all patients.